Fungitoxic potential of Vernonia amygdalina and Cymbopogon citratus extraction methods and concentrations on Fusarium proliferatum of Rice (Oryza sativa) (Agriculture, Food, and Natural Resources Journal, 2025)
This study evaluated the fungitoxic efficacy of Vernonia amygdalina (bitter leaf) and Cymbopogon citratus (lemon grass) extracts against Fusarium proliferatum, a significant pathogen affecting rice production. Treatments comprised of 2 plants (bitter leaf and lemongrass) extracted using 2 methods (Soxhlet and Maceration) at 4 concentrations (0%, 50%, 75%, and 100%) respectively to assess their inhibitory effects on fungal radial growth over a 7-day period. The experiment employed a 2 × 2 × 4 factorial laid in a completely randomized design with three replications. Analysis of variance revealed significant main effects (p
Keywords: Antifungal; Cymbopogon citratus; Extract; Fusarium proliferatum; Rice